Subsequent Acupuncture Reverses the Aftereffects of Intermittent Theta-Burst Stimulation - He, Xiao-Kuo; Liu, Hui-Hua; Chen, Shan-Jia; Sun, Qian-Qian; Yu, Guo; Lei, Lei; Niu, Zhen-Yuan; Chen, Li-Dian; Hsieh, Tsung-Hsun (Frontiers in Neural Circuits, 2021)
Objective This study explored whether acupuncture affects the maintenance of long-term potentiation (LTP)-like plasticity induced by transcranial magnetic stimulation (TMS) and the acquisition of motor skills following repetitive sequential visual isometric pinch task (SVIPT) training. Methods Thirty-six participants were recruited. The changes in the aftereffects induced by intermittent theta-burst stimulation (iTBS) and followed acupuncture were tested by the amplitude motor evoked potential (MEP) at pre-and-post-iTBS for 30 min and at acupuncture-in and -off for 30 min. Secondly, the effects of acupuncture on SVIPT movement in inducing error rate and learning skill index were tested. Results Following one session of iTBS, the MEP amplitude was increased and maintained at a high level for 30 min. The facilitation of MEP was gradually decreased to the baseline level during acupuncture-in and did not return to a high level after needle extraction. The SVIPT-acupuncture group had a lower learning skill index than those in the SVIPT group, indicating that acupuncture intervention after SVIPT training may restrain the acquisition ability of one’s learning skills. Conclusion Acupuncture could reverse the LTP-like plasticity of the contralateral motor cortex induced by iTBS. Subsequent acupuncture may negatively affect the efficacy of the acquisition of learned skills in repetitive exercise training.